(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
The kaizen is considered as one of the most important modern techniques which has been adopted by various economics entities especially manufacturing firms and its beginnings return to the middle of the earlier century that has been used by companies like Toshiba, Matsushita Electric, and Toyota. Which realized that these modern techniques would make a total change in the competitive environment and started qualifying and its staff in such away that enables them to go along with this unique environment. The continuous improvement (Kaizen) depends on the small continuous improvements in the product and the production operations during the production stage. Consequently, the research problem is represented in the improperly of the budgeting estimations for the performance evaluation unless these estimations are adjusted by the expected changes in costs as a result for the kaizen technique usage which becomes indispensable today for competition. So, this research aims at studying and analyzing the modern approaches in the budgeting preparation in the contemporary competitive environment. Also, the study of modern techniques have been used in reducing costs for products and serving the economical entities for facing the strong competition in the market. Besides, showing the expected effects for using the modern techniques for reducing costs on the budgeting estimations and its reflection on the control and performance evaluation. To achieve this purpose, the research has been divided into four main branches. The first is devoted to the research methodology. The second deals with the concept and the nature of kaizen. The study of the activity of the budgeting as advice for control and performance evaluation in the continuous improvement have been dealt with in the third branch. The forth one has been devoted for the most important conclusions and the recommendations.